(untitled) (Research, Society and Development, 2022)
Objective: To carry out an assessment of the perception, knowledge and behavior of schoolchildren in the municipality of Nova Soure, Bahia, through COVID-19. Methods: A cross-sectional and descriptive epidemiological study was carried out with high school students from Colégio Estadual Professora Maria De Lourdes Ferreira da Silva. After voluntarily joining the study, students received a questionnaire in the form of Google Forms, distributed by WhatsApp, consisting of 40 objective questions, with the aim of evaluating socioeconomic data, perceptions, knowledge, routine, habits, behaviors performed in the face of the pandemic on the COVID-19. Results: Regarding sociodemographic characteristics, 154 (56.7%) were female and 125 (43.3%) were male. The majority lived in the urban area 166 (57.4%) while the others lived in the rural area 123 (42.6%). Many were informed about the pandemic on the internet, 171 (59.2%) and 114 (39.4%) on TV. Most were physically active during the pandemic period 188 (65.1%) and 225 (77.9%) often left home during this period. Conclusion: The research developed showed that the use of technologies in the teaching and learning process contributes a lot to education; however, it was also observed that the pandemic accentuated disparities in relation to access to education.